The effect of M3 monetary aggregates and bank loans on the economic growth of countries in the Eurozone, the USA and Japan - Černohorská, Liběna; Kula, Vojtěch (Univerzita Pardubice, 2017)
This paper examines the influence of selected indicators of the banking sector (M3 monetary aggregates and bank loans provided to the non-financial private sector) on economic growth (GDP) in the Eurozone, the USA and Japan. Cointegration of these selected indicators of the banking sector has been demonstrated in relation to the development of GDP using the Engle - Granger cointegration test. These tests were applied to selected statistical data from the years 2000 to 2015. The first was to determine the optimum delay using Akaike criteria for all-time series analysed. Then the presence of a unit root was analysed using the Dickey - Fuller test. Based on the test results, time series were excluded which appear to be stationary. If the conditions were met, testing then continued with the Engle - Granger test to detect cointegration relations, which would determine a relationship between selected variables. Based on these tests, it was found that at a significance level of 0.05, no cointegration relationship exists between any of the time series in the countries surveyed.
Keywords: banking sector; cointegration test; economic growth; GDP; M3; E51; E47; C32